STED nanoscopy of the centrosome linker reveals a CEP68-organized, periodic rootletin network anchored to a C-Nap1 ring at centrioles - Vlijm, Rifka; Li, Xue; Panić, Marko; Rüthnick, Diana; Hata, Shoji; Herrmannsdörfer, Frank; Kuner, Thomas; Heilemann, Mike; Engelhardt, Johann; Hell, Stefan; Schiebel, Elmar (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The centrosome linker proteins C-Nap1, rootletin, and CEP68 connect the two centrosomes of a cell during interphase into one microtubule-organizing center. This coupling is important for cell migration, cilia formation, and timing of mitotic spindle formation. Very little is known about the structure of the centrosome linker. Here, we used stimulated emission depletion (STED) microscopy to show that each C-Nap1 ring at the proximal end of the two centrioles organizes a rootletin ring and, in addition, multiple rootletin/CEP68 fibers.